1986
DOI: 10.1056/nejm198608283150906
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Survival and Age at Diagnosis in Breast Cancer

Abstract: We analyzed the relation between age at diagnosis and relative survival (ratio of observed to expected survival) in 57,068 women in Sweden in whom breast cancer was diagnosed in 1960 to 1978 (about 98 percent of all cases). Women who were 45 to 49 years old had the best prognosis, with a relative survival exceeding that of the youngest patients (less than 30 years) by 7.6 to 12.9 percent at different periods of observation. Relative survival declined markedly after the age of 49--particularly in women aged 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

34
213
4
15

Year Published

1987
1987
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 482 publications
(273 citation statements)
references
References 20 publications
34
213
4
15
Order By: Relevance
“…Tamoxifen was found to be associated with a 10% reduction in the RER of death compared with ER þ women not prescribed the drug (results not presented) -a figure consistent with reductions reported elsewhere (Early Breast Cancer Trialists' Collaborative Group, 1998). We note that women in the 40 -49 age class (predominantly premenopausal) had the lowest RER of death, consistent with previous findings (Langlands and Kerr, 1979;Adami et al, 1986;Sant et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…Tamoxifen was found to be associated with a 10% reduction in the RER of death compared with ER þ women not prescribed the drug (results not presented) -a figure consistent with reductions reported elsewhere (Early Breast Cancer Trialists' Collaborative Group, 1998). We note that women in the 40 -49 age class (predominantly premenopausal) had the lowest RER of death, consistent with previous findings (Langlands and Kerr, 1979;Adami et al, 1986;Sant et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…This correlates with the poor prognosis of breast cancer in older patients. 23 Although some authors 24 have reported young age to be adverse prognostic factor, in the present study, younger patients showed more of positive E-CD expression. This is due to the fact that older patients generally present at a locally advanced stage, in contrast to younger patients presenting at a relatively earlier stage.…”
Section: Discussioncontrasting
confidence: 58%
“…Studies examining this issue have varied in design, age categorization and outcome measures. A few large population-based studies and more limited analyses [1][2][3][4][5] have indicated that women under the ages of 30 -40 years have a worse prognosis. Some retrospective studies have attempted to explain the less favorable outcome in younger women and have reported that breast cancers in younger women exhibit more adverse characteristics, including a high clinical stage at diagnosis, high histologic grade, lack of steroid hormone receptors and increased proliferation.…”
mentioning
confidence: 99%